Microsoft Expression Design on demand - LoCascio, Ted (Que Pub., 2008)
Microsoft Expression Design on Demand FOR THOSE WHO WOULD RATHER BE SHOWN HOW THAN TOLD HOW SEE HOW TO: Create, open, and save Expression Design documents; Navigate documents easily by zooming and scrolling; Understand how to use the Expression Design interface controls; Align objects by snapping to grids, guides, and points; Select objects, path segments, and points with the various selection making tools; Arrange, align, distribute, and stack objects on the artboard; Control object visibility and position using Layers panel controls; Draw shapes and paths using the various drawing tools, such as the Pen, B-spline, and Polyline tools; Apply object attributes such as fills, strokes, and effects; Incorporate bitmap images and graphics into your designs; Create and format editable text objects; Export in various formats such as XAML, GIF, JPEG, TIFF, and PDF On the Web This book uses real world examples to give you a context in which to use the task. This book also includes workshops to help you put together individual tasks into projects. The Expression Design example files that you need for project tasks are available at www.informit.com/title/0789738260 Ted LoCascio is a professional graphic designer who served as senior designer at KW Media and the National Association of Photoshop Professionals (NAPP) for several years. He has created layouts, graphics, and designs for many successful software training books, videos, websites, and magazines. Ted is the author of numerous books and has contributed articles to Photoshop User magazine, Creativepro.com, the Quark Xtra newsletter, PlanetQuark.com, and InDesign Magazine. He has also taught at the Adobe CS Conference, the InDesign Conference, the Pixel Conference, the Vector Conference, and PhotoshopWorld. A graphic designer for more than ten years, Ted's designs and illustrations have been featured in several national newsstand and trade magazines, books, and various advertising and marketing materials.
Print version record
Keywords: Microsoft Expression Design; Computer graphics; Infographie; computer graphics